Factors Influencing Prenatal Care Behaviour of Pregnant Women In Kembaran II Primary Health Center - Lies Oktorita, A; Gamelia, E; Purnamasari, D U; Susanna, D (KnE Life Sciences, 2019)
Pregnancy is a natural process that will be experienced by women that takes within 280 to 300 days. During pregnancy the pregnant woman requires proper supervision. Kembaran II Primary Health Center in 2014 had 3 cases of maternal mortality, and the number of high-risk pregnant women was 48%. The purpose of this research was to analyze the factors that influenced to prenatal care behavior of pregnant women in Kembaran II Primary Health Center. This research used a quantitative cross-sectional approach. The population of study was 102 pregnant women. Sampling technic used Simple Random Sampling to third-trimester pregnant women, and the sample was 80 people. Data collection was performed by interviewing and questionnaire. To analyze the data, comprise of univariate, bivariate, it used chi-square and for multivariate, it used regression logistics test. Univariate test showed the majority of respondents were in no risk of age (78.8%), the level of primary education (55%), primiparous parity pregnancies (35 %), did not work (58.8%), per capita income (<IDR 574.923) (8.8%), had a good knowledge (7.5%), had right attitude (56.3%), good family support (57.5%), information exposure (67.5%) and inadequate prenatal care behavior (51.3%). Bivariate test results showed information exposure related to fetal care behavior (p = 0.013). The results of multivariate test showed that the variables of family support (p=0.009) and information exposure (p=0.045) affected the prenatal care behavior of pregnant women in Kembaran II Primary Health Center. Information about prenatal care, especially personal hygiene, pregnancy crisis, consumption of nutrients should be increased. Keywords: Pregnant women; prenatal care behavior; information exposure; family support